PSEUDOMEMBRANOUS COLITIS: DIAGNOSIS, TREATMENT AND PREVENTION - T. V. Chyornenkaya (Неотложная медицинская помощь, 2016)
In recent years, Clostridium difficile has become one of the most common and aggressive nosocomial pathogens. The toxigenic strain of C. difficile is the etiological agent of pseudomembranous colitis. This disease leads to the development of dangerous complications without proper therapy. To prevent the C. difficile infection, optimization of in-hospital antibiotics usage and strict compliance with principles of infection control are required. The review of literature presents modern approaches to diagnosis, treatment and prevention of infections, caused by C. difficile.